Emerging challenges in business, optimization, technology, and industry : proceedings of the Third International Conference on Business Management and Technology, Vancouver, BC, Canada 2017 /: proceedings of the Third International Conference on Business Management and Technology, Vancouver, BC, Canada 2017. (2018) - Unknown
No abstract available